Education and health care provision in the Romanian Danube Valley: Territorial disparities. Issue 2 (12th July 2018) - Damian, Nicoleta; Mocanu, Irena; Mitrică, Bianca
Abstract: The Romanian Danube Valley is an integral part of the Danube Region. According to the EU Strategy for the Danube Region (EUSDR), a healthy and well‐educated population is the key issue for sustainable and coherent development of this territory. This paper aims to explore, at micro‐scale level (Local Administrative Units 2 – LAU2), the population's responsivity to health care and education provision according to the demographic characteristics. By using the official statistical data available at a local level and the results provided by the TEMPO‐Online time‐series published by the National Institute of Statistics in 2015, the study assesses current education and health care provision in the Romanian Danube Valley, following the micro‐scale responsivity of the population. The authors have selected some specific statistical indicators in order to highlight education and health care provision and the population's responsivity. The indicators are normalised and gathered in the Education and Health Care Provision Index and the Education and Health Care Responsivity Index. This study shows that the majority of the Danubian LAU2 registered more users of the education and health care services than being available along the Valley. It also highlights the interrelation between low education and health care provision level and poor social and economic opportunities, and therefore the loss of market efficiency, marginalising some groups and reinforcing existing inequalities. Abstract : This article aims to explore, at micro‐scale level (LAU2), the population's responsivity to health care and education provision according to the demographic characteristics. This study shows that the majority of the Danubian LAU2 registered more users of the education and health care services than being available along the Valley. It also reflects the interrelation between low education and health care provision level and the poor social and economic opportunities.